Potential correlation between volatiles and microbiome of Xiang xi sausages from four different regions. (January 2021) - Yu, Meijuan; Xiang, Xiaole; Tan, Huan; Zhang, Qun; Shan, Yang; Yang, Hui
Graphical abstract: Highlights: Key (main and differential) volatiles of Xiangxi sausages characterized by GC-IMS and multivariate analysis. Esters, olefins and Sau., Ltb., DM. AG. were the dominant volatiles and microbiome . 48 (28P & 20) pair-wise correlations among 31 volatiles and 10 bacteria were found in Xiangxi sausages. 28 (13P & 15N) pair-wise correlations among 11 volatiles and 9 fungi were obtained in Xiangxi sausages. ST.,   PM.  ( DM. ) and  LN. ( AN. ) were positively and negatively related to volatiles. Abstract: Volatiles and microbiome from different Xiang xi sausages (HBD, HBN, HHY and HDK) were performed by Chromatography-Ion Mobility Spectrometry and Illumina MiSeq platform (16 S rRNA and ITS sequencing). Results indicated that ethanol, ethyl acetate, ethyl-propanoate, pinene, limonene, cineole, etc. were the key (main) volatiles; whereas staphylococcus, lactobacillus, solanum-torvum, brochothrix and debaryomyces, candida were the dominant bacteria and fungi, respectively. The variation and relationship between microbiome and volatiles were disclosed by multivariate and spearman's correlation analysis. Volatiles of HDK is similar to HBN and HBD compared to HHY, while microbiome community of HHY is similar to HBN and HDK compared to HBD. Solanum-torvum, pseudomonas (bacteria) and debaryomyces (fungi) contributed positively to the development of major volatiles in Xiangxi sausages. Meanwhile, 'carbohydrate metabolism', 'amino acid metabolism' (microbia) and glycolysis/gluconeogenesis (volatiles) were commented in KEGG database. This study provides a deep insight into the relation between volatiles and microbiome (bacteria and fungi) of Xiangxi sausages.